Replication Data for: Effect of ice sheet thickness on formation of the Hiawatha impact crater - Silber, Elizabeth
The iSALE simulation input files and compressed model outputs for "Effect of ice sheet thickness on formation of the Hiawatha impact crater", published in EPSL; Authors: Silber, E. A., Johnson, B. C., Bjonnes, E., MacGregor, J. A., Larsen, N. K., Wiggins, S. E. (2021)